Protective effect of adiponectin on oxidative stress-induced ovarian granulosa cell senescence in geese - Yan Zheng; Yunqiao Qiu; Ming Gao; Qianhui Wang; Lei Yu; Zhongzan Cao; Xinhong Luan (Poultry Science)
Geese are susceptible to oxidative stress during breeding, leading to senescence of granulosa cells (GCs) and reduced egg production. Adiponectin (ADPN) is a cytokine secreted by adipose tissue that functions to regulate metabolism and antioxidants. However, its role in the regulation of goose GCs is unclear. To investigate this, senescence in primary goose GCs was induced by D-gal and assessed via RT‒qPCR, senescence-associated β-galactosidase (SA-β-gal) staining, immunofluorescence, flow cytometry, and transcriptomics. The effect of ADPN on GC senescence was investigated by overexpressing and knocking down ADPN expression. The results showed that ADPN could alleviate oxidative stress and cell cycle arrest in GCs, reduce the expression of the senescence-associated secretory phenotype (SASP)-related genes IL-6 and IL-8, regulate the metabolic capacity of GCs, reduce the accumulation of SA-β-gal, maintain telomere length, and alleviate the senescence of GCs induced by D-gal. The RNA-seq results provided further evidence for the regulatory effect of ADPN on GC senescence. ADPN was shown to attenuate oxidative stress-induced GC senescence through the AGE (Advanced glycation end products)-RAGE (Receptor of advanced glycation end products) and NOD-like receptor pathways. These findings may contribute to the development of improved theoretical references for improving egg-laying performance and prolonging the service life of geese.